Endurance and sprint benefits of high-intensity and supramaximal interval training - Cicioni-Kolsky, D.; Lorenzen, C.; Williams, M. D.; Kemp, J. G. (European Journal of Sport Science, 2013)
This study examined the effect of two different interval training programs-high-intensity interval training (HIT) and supramaximal interval training (SMIT)-on measures of sprint and endurance performance. Physically active individuals (Females: n=32; age 19.3, s=2.2 years; mass 67.6, s=9.1 kg; stature 172.7, s=6.6 cm. Males: n=23; age 20.0, s=2.7 years; mass 71.3, s=8.3 kg; stature 176.6, s=5.8 cm) completed pre-testing that comprised (1) 3000 m time-trial, (2) 40 m sprint, and (3) repeated sprint ability (RSA-6×40 m sprints, 24 s active recovery) performance. Participants were then matched for average 3000 m running velocity (AV) and randomly assigned to one of three groups: (i) HIT, n=19, 4 min at 100% AV, 4 min passive recovery, 4-6 bouts per session; (ii) SMIT, n=20, 30 s at 130% AV, 150 s passive recovery, 7-12 bouts per session; and (iii) control group, n=16, 30 min continuous running at 75% AV. Groups trained three times per week for six weeks. When time to complete each test were compared among groups: (i) improvements in 3000 m time trial performance were greater following SMIT than continuous running, and (ii) improvements in 40 m sprint and RSA performance were greater following SMIT than HIT and continuous running. In addition, a gender effect was observed for the 3000 m time trial only, where females changed more following the training intervention than males. In summary, for concurrent improvements in endurance, sprint and repeated sprint performance, SMIT provides the greatest benefits for physically active individuals.